Work order for supply, installation and commissioning of stainless steel sheet cladding on the wall around lift opening for the BRACU new campus project at holding no. Kha 224,Merul Badda,Dhaka-1212. - Brac University (Brac University, 2023)
This purchase order has been made between M R Corporation for supply, installation and commissioning of stainless steel sheet cladding on the wall around lift opening for the BRACU new campus project